Evaluation of ferrock: A greener substitute to cement. (2020) - Vijayan, D.S.; Dineshkumar; Arvindan, S.; Shreelakshmi Janarthanan, Thattil
Abstract: Concrete, the second most used entity after water around the globe which accounts for 8 to 10% of total CO2 emissions is mainly due to cement. This proposes to evaluate the ability of Ferrock to be used as one of the best possible substitute for cement in concrete. It is an iron based binding compound which utilises variety of waste materials to form a carbon negative building material. Iron dust (a waste from iron industries) which would otherwise end up in landfills is used along with small proportions of limestone, fly ash and meta -kaolin to make this novel substance. Our study compares the environmental impacts of ordinary Portland cement and Ferrock (iron dust 60%, fly ash 20%, Metakoalin 12% and limestone 8%) focussing specially on their contribution to carbon pollution, water use and energy consumption. By substituting cement with Ferrock in varying proportions as 4%, 8%, and 12% in concrete we are trying to find the optimum ratio of replacement which would give desired results in both strength (compressive, split tensile & flexural tested) along with sustainability. In all the test result which is comperes 8% which shows the good result in strength.